Nutritional marine life - Ramasamy Santhanam (London CRC Press, 2024)
The nutritional benefits of marine flora and fauna are well known. Fish and crustaceans provide high-quality sources of amino acids-nutritionally important proteins found in only small amounts in cereals and grains. Nutrients and minerals in seafood can improve brain development and reproduction and there are strong links between fish and heart heal.
Keywords: Food Technology